Design and fabrication of automatic recycle bin / Muhammad Iqbal Wafiuddin Johar - Johar, Muhammad Iqbal Wafiuddin (2023)
Many recyclable waste are not thrown into their own categories that will result in making the environment unhealthy. So, the objective is to develop an automatic recyclable bin that will sort out the waste thrown correctly into their own categories without any need of pushing button or pulling a lever. The bin consists of containers for each type of waste and sensors to identify every type of waste thrown into the automatic recycle bin. Then, a separator will separate the waste into their own containers with the help of servo motors. This project will reduce pollutions and can save cost by reducing the need to produce the same item with the same materials. In conclusion, people will learn that recycling are important to create a healthier environment for living things.